Emotional Dysregulation and Anxiety Control in the Psychopathological Mechanism Underlying Drive for Thinness - Fiore, Francesca; Ruggiero, Giovanni M.; Sassaroli, Sandra (Frontiers in Psychiatry, 2014)
Emotional dysregulation is a process which consists in mitigating, intensifying or maintaining a given emotion and is the trigger for some psychological disorders. Research has shown that a anxiety control plays an important role in emotional expression and regulation and, in addition, for anorexia nervosa and, more in general, in drive for thinness. Scientific literature suggests that in anorexia nervosa there is a core of emotional dysregulation and anxiety control. The aim of this study is to explore the roles of emotional dysregulation and anxiety control as independent or third variables in a mediational regression model related to drive for thinness. 154 clinical individuals with anorexia participated in the study and all completed a set of self-report questionnaires: eating disorders inventory version 3 (EDI-3), DERS, and the anxiety control questionnaire (ACQ). The data confirmed a mediational model in which the relation between emotional dysregulation and drive for thinness is mediated by anxiety control. The current study partially supports a clinical model in which emotional dysregulation is a distal factor in eating disorders while the mediator variable anxiety control is a proximal factor in the psychopathological process underlying it.